Analisis Kemampuan Pemecahan Masalah Berdasarkan Teori Polya dalam Menyelesaikan Soal Materi Perbandingan - Aflah, Tania; Maimunah, Maimunah; Roza, Yenita (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study is to describe the problem-solving ability in comparative materials, especially in story problems. The ability to solve problems by using the strategy of polya theory, namely: understanding the problem, making a plan, implementing the plan and re-examining. The research method used is qualitative descriptive. The data collection techniques used in this study are written tests and interviews. The subjects of this study include 3 grade VII students of SMP Negeri 48 Pekanbaru who have been taught comparative material. The research instruments used are description tests and interview guidelines. The results of the study showed that (1) students with high academic abilities were able to understand problems, plan problem solving, implement solution plans, and recheck answers according to Polya stages. (2) Students with medium academic ability are only able to understand problems, plan and implement problem solving plans, but are not able to recheck the answers. (3) Students with low academic ability have difficulty understanding problems, do not write down a solution plan, have difficulty doing calculations, and are unable to recheck answers.